IS1630 of Mycoplasma fermentans, a Novel IS30-Type Insertion Element That Targets and Duplicates Inverted Repeats of Variable Length and Sequence during Insertion - Calcutt, Michael J. (American Society for Microbiology, 1999)
A new insertion sequence (IS) of Mycoplasma fermentans is described. This element, designated IS1630, is 1,377 bp long and has 27-bp inverted repeats at the termini. A single open reading frame (ORF), predicted to encode a basic protein of either 366 or 387 amino acids (depending on the start codon utilized), occupies most of this compact element. The predicted translation product of this ORF has homology to transposases of the IS30 family of IS elements and is most closely related (27% identical amino acid residues) to the product of the prototype of the group, IS30. Multiple copies of IS1630 are present in the genomes of at least two M. fermentans strains. Characterization and comparison of nine copies of the element revealed that IS1630 exhibits unusual target site specificity and, upon insertion, duplicates target sequences in a manner unlike that of any other IS element. IS1630 was shown to have the striking ability to target and duplicate inverted repeats of variable length and sequence during transposition. IS30-type elements typically generate 2- or 3-bp target site duplications, whereas those created by IS1630 vary between 19 and 26 bp. With the exception of two recently reported IS4-type elements which have the ability to generate variable large duplications (B. B. Plikaytis, J. T. Crawford, and T. M. Shinnick, J. Bacteriol. 180:1037–1043, 1998; E. M. Vilei, J. Nicolet, and J. Frey, J. Bacteriol. 181:1319–1323, 1999), such large direct repeats had not been observed for other IS elements. Interestingly, the IS1630-generated duplications are all symmetrical inverted repeat sequences that are apparently derived from rho-independent transcription terminators of neighboring genes. Although the consensus target site for IS30 is almost palindromic, individual target sites possess considerably less inverted symmetry. In contrast, IS1630 appears to exhibit an increased stringency for inverted repeat recognition, since the majority of target sites had no mismatches in the inverted repeat sequences. In the course of this study, an additional copy of the previously identified insertion sequence ISMi1 was cloned. Analysis of the sequence of this element revealed that the transposase encoded by this element is more than 200 amino acid residues longer and is more closely related to the products of other IS3 family members than had previously been recognized. A potential site for programmed translational frameshifting in ISMi1 was also identified.